Determinants of Self-reported Health among Older Adults in Thailand - Senkrua, Akkaya (Journal of Business, Innovation and Sustainability (JBIS), 2025)
Background Rapidly aging societies have become one of the most concerning issues that many countries, including Thailand, are now facing. Thailand is now in the stage of population aging in which the working-age share of the population is shrinking and the older-age share is increasing. Understanding the factors that influence health outcomes among the elderly becomes increasingly important. As people live longer, ensuring they maintain good health is essential to reduce the burden on healthcare systems and society. Methods This study utilizes data from the 2021 Survey of the Older Persons in Thailand collected by National Statistics Office (NSO). The study focuses on a person aged sixty years and above, defined as an older adult, resulting in a sample of 43,693 older persons. The binary logistic regression analysis was used to determine how demographic, economic, behavior and social environment factors affect elderly health. Results For each additional year of age, the probability of having good health decreases. Males are more likely to have good health compared to females. Individuals with higher education are more likely to have good health compared to those with lower education. Universal healthcare has the least impact on good health. Older adults who can do activities of daily living without dependence and those exercise regularly have higher probability to have good health. Elderly living alone slightly decreases the likelihood of good health. Older adults who quit jobs deteriorated health.